2009
DOI: 10.1007/s12548-009-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Axiography and MRI in the diagnosis of temporomandibular joint pathology

Abstract: Aim of the study was to compare the Magnetic Resonance Imaging (MRI) and the Computerized Axiography tracings to find out the agreement of the two exams. The results showed that the agreement was very low. MRI and Computerized Axiography record different characteristics of the joints being the MRI a static and the Axiography a dynamic exam. They should be considered complementary and both necessary for a full diagnosis of Temporo-Mandibular Joint Pathology.Keywords: Magnetic resonance imaging, axiography, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Piancino et al ( 31 ) previously analyzed the association between computerized axiography and MRI data, which yielded a very low kappa index of 13%. They then concluded that MRI and computerized axiography are two completely different types of examination methods that should instead be used in conjunction with one another ( 31 ). The same conclusion has also been reached by Piehslinger et al ( 32 ), who obtained a concordance of only 45% between MRI and computerized axiography.…”
Section: Discussionmentioning
confidence: 99%
“…Piancino et al ( 31 ) previously analyzed the association between computerized axiography and MRI data, which yielded a very low kappa index of 13%. They then concluded that MRI and computerized axiography are two completely different types of examination methods that should instead be used in conjunction with one another ( 31 ). The same conclusion has also been reached by Piehslinger et al ( 32 ), who obtained a concordance of only 45% between MRI and computerized axiography.…”
Section: Discussionmentioning
confidence: 99%
“…MRI provides a better visibility of joint morphology in image form, as sometimes clinical diagnosis does not provide a clear picture [12,13]. Several studies have compared clinical TMD diagnosis and MRI findings of TMJs, and different results have been obtained, and the agreement between specific clinical diagnosis and MRI findings has been fair to poor [14][15][16]. In particular, it is not clear whether the change in disc position observed upon MRI correlates with the dynamic findings of the condylar movements during function.…”
Section: Introductionmentioning
confidence: 99%
“…Однако ее использование для диагностики этих расстройств было поставлено под сомнение из-за значительной вариабельности результатов, описанных в литературе (Klasser and Okeson, 2006) [5]. В исследованиях, посвященных диагностике различных состояний здоровья, оценивалась точность и корреляция различных инструментов оценки для определения референсных значений и наилучшей формы диагностики (Manfredini и др., 2011; De Felício и др., 2012; Reneker и др., 2011; Piancino и др., 2012) [6][7][8][9]. Хотя показатели поверхностной ЭМГ используются в качестве данных дополнительного обследования при диагностике дисфункций височно-нижнечелюстного сустава, предыдущие исследования продемонстрировали низкое методологическое качество, в них не были описаны методология, инструменты и интерпретация данных, а также отсутствовали референсные значения, позволяющие дифференцировать людей с дисфункцией ВНЧС и без неё (Gonzalez et al, 2008) [10].…”
unclassified